Do Geopolitical Shocks Shape Sectoral Stock Performance? Evidence from Indonesia’s Emerging Market - Anggi Mayang Sari; Linda Karlina Sari; Tanti Novianti (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Geopolitical shocks have emerged as a significant determinant of market volatility and abnormal returns, particularly in emerging markets such as Indonesia. Sectoral indices in the Indonesia Stock Exchange (IDX) respond differently to domestic and global political events, reflecting varying levels of exposure and resilience.Purpose: This study aims to examine how major geopolitical events affect sectoral stock performance in Indonesia, providing empirical insights for understanding market sensitivity and formulating central bank policy responses.Design/methodology/approach: Using the event study methodology and the Market Adjusted Model (MAM), this research analyzes abnormal returns (AR) and cumulative abnormal returns (CAR) for ten sectoral indices on the IDX from 2018 to 2025. Seven geopolitical events are observed, including Indonesia’s presidential election, the U.S. presidential inauguration, and bilateral trade negotiations between Indonesia and the U.S. A 120-day estimation window and three event windows (±2, ±5, and ±10 days) are applied to capture short-term market reactions.Findings/Result: The findings reveal that the finance, healthcare, and basic materials sectors experienced statistically significant abnormal returns, particularly within the ±10-day window, indicating higher exposure to policy-related uncertainty and global sentiment shifts. The technology sector showed notable fluctuations but lacked statistical significance. In contrast, non-cyclical and cyclical sectors demonstrated muted responses, suggesting their defensive market nature.Conclusion: The results highlight that sectoral responses to geopolitical shocks are asymmetric across industries. These variations underscore the importance of developing more granular and sector-specific financial stability measures. Central bank communication, stress testing with geopolitical risk parameters, and coordination with fiscal authorities are essential to mitigating systemic risks.Originality/value (State of the art): This study extends the limited literature on geopolitical-financial linkages in Southeast Asian emerging markets by offering a sectoral perspective. It provides actionable policy insights for central banks in managing financial stability under rising geopolitical uncertainty. Keywords:   abnormal return, behavioral finance, emerging markets, event study, geopolitical risk